Investigation of a multi-biomarker disease activity score in rheumatoid arthritis by comparison with magnetic resonance imaging, computed tomography, ultrasonography, and radiography parameters of inflammation and damage. (3rd September 2017) - Krabbe, S; Bolce, R; Brahe, CH; Døhn, UM; Ejbjerg, BJ; Hetland, ML; Sasso, EH; Chernoff, D; Hansen, MS; Knudsen, LS; Hansen, A; Madsen, OR; et al.
Abstract : Objectives : To investigate the multi-biomarker disease activity (MBDA) score by comparison with imaging findings in an investigator-initiated rheumatoid arthritis (RA) trial (HURRAH trial, NCT00696059). Method : Fifty-two patients with established RA initiated adalimumab treatment and had magnetic resonance imaging (MRI), ultrasonography (US), computed tomography (CT), and radiography performed at weeks 0, 26, and 52. Serum samples were analysed using MBDA score assays and associations between clinical measures, MBDA score, and imaging findings were investigated. Results : The MBDA score correlated significantly with MRI synovitis (rho = 0.65, p < 0.001), MRI bone marrow oedema (rho = 0.36, p = 0.044), and US power Doppler (PD) score at week 26 (rho = 0.35, p = 0.039) but not at week 0 or week 52. In the 15 patients who had achieved a Disease Activity Score based on C-reactive protein (DAS28-CRP) < 2.6 at week 26, MRI and/or US detected subclinical inflammation and 13 (87%) had a moderate/high MBDA score. For the cohort with available data, none of the four patients in MBDA remission (score ≤ 25) at week 26 had progression of imaging damage from baseline to week 52 whereas progression was observed in three out of nine (33%) and seven out of 21 (33%) patients with moderate (30–44) and high (> 44) MBDA scores, respectively. Conclusions : In this cohort, the MBDA score correlated poorly with MRI/US inflammation. However, the MBDA score and MRI/US were generally concordant in showing signs of inflammation in most patients in clinical remission during anti-tumour necrosis factor (anti-TNF) therapy. MBDA scores were elevated in all patients with structural damage progression.